Joyful Literacy Learning Opportunities for Kindergarten Educators: Using Design-Based Research to Build Collaborative Educator-Research Partnerships - Messenger, Yvonne; Gallagher, Tiffany (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
In this study, Ontario kindergarten educators (n=10) describe their tensions related to approaches for early literacy learning and how enhanced self-efficacy supported their navigation for blending direct and play-based instructional approaches for early literacy instruction. Following design-based research methodology, educators participated in interviews and professional learning conversations to identify their needs for teaching beginning reading. Findings include: 1) collaborating with educators and the researcher/facilitator brought participants joy, 2) changing messages from education leaders created challenges, 3) self-efficacy beliefs increased, 4) educators noticed a change in the types of play opportunities that supported literacy learning. Implications and recommendations are discussed for researchers, educators, and school board leaders.